Application of Motorcycle Service Queuing Models and Simulations in Aur Kuning - Gerli Wira Yudha; Gina Hadai Yani Fitri; Latifa Humaira; Hafiz An Naufal; Fadhilah Yuliarizman; Liza Efriyanti (BiCED Proceeding, 2024)
Queue simulation is important for analyzing and optimizing service processes in various fields such as bank counter queue services, gas station vehicle queues, vehicle queues in parking lots including motorcycle repair shop service queues. In this case, the research objective is to propose the application of queuing simulation to identify and improve service efficiency in motorcycle maintenance workshops. With the right simulation model, we can analyze various aspects of motorcycle workshop operations, from customer waiting time to efficient resource utilization. This research investigates the use of queuing simulation in motorcycle repair shops, focusing on identifying and addressing potential bottlenecks in the service process. By collecting sample data from 30 incoming vehicles split over three days, we created a representative simulation model for a motorcycle repair shop. With the results of this simulation can help workshop owners in overcoming or getting a solution to the problem of motorcycle queues, this case study will contribute so that there is a change to the effectiveness of motorcycle workshops in the queue by developing the results of this article, keyword model, simulation, queue, motorcycle.